2017
DOI: 10.3390/rs9070748
|View full text |Cite
|
Sign up to set email alerts
|

Criteria Comparison for Classifying Peatland Vegetation Types Using In Situ Hyperspectral Measurements

Abstract: This study aims to evaluate three classes of methods to discriminate between 13 peatland vegetation types using reflectance data. These vegetation types were empirically defined according to their composition, strata and biodiversity richness. On one hand, it is assumed that the same vegetation type spectral signatures have similarities. Consequently, they can be compared to a reference spectral database. To catch those similarities, several similarities criteria (related to distances (Euclidean distance, Manh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
56
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(63 citation statements)
references
References 130 publications
6
56
1
Order By: Relevance
“…The selected VI were finally tested to discriminate among treatments using L 2 -Regularized Logistic Regression (RLR), also known as Ridge regression (Friedman & Popescu 2004, Hoerl & Kennard 1970. RLR has been widely used for classification purposes in various domains including remote sensing (Tuia et al 2016, Zhang et al 2015, and revealed to be efficient when applied on vegetation (Erudel et al 2017). We only trained the RLR classifier at leaf scale to assess the robustness of VI at higher acquisition scales.…”
Section: Vegetation Indicesmentioning
confidence: 99%
“…The selected VI were finally tested to discriminate among treatments using L 2 -Regularized Logistic Regression (RLR), also known as Ridge regression (Friedman & Popescu 2004, Hoerl & Kennard 1970. RLR has been widely used for classification purposes in various domains including remote sensing (Tuia et al 2016, Zhang et al 2015, and revealed to be efficient when applied on vegetation (Erudel et al 2017). We only trained the RLR classifier at leaf scale to assess the robustness of VI at higher acquisition scales.…”
Section: Vegetation Indicesmentioning
confidence: 99%
“…In order to assess the accuracy of our approach, the results were compared to those obtained with approaches directly linking TPH concentrations to leaf reflectance in the VIS, including pigmentrelated vegetation indices (listed in [65]) and partial least square regression (PLSR) with reflectance transformation (derivatives, continuum removal, etc.) [12,27].…”
Section: Variability Of Leaf Pigment Contents and Tph Estimationmentioning
confidence: 99%
“…This provided a 1 m resampled reflectance image with 409 spectral bands covering the reflective domain (400-2500 nm). Because of the low signal-to-noise ratio (SNR), we did not conserve the bands with atmospheric transmission below 80%, as described in [49]. A Savitzky-Golay smoothing filter [50] was applied to improve the SNR at the remaining bands, and the final 1 m georeferenced reflectance image was used for calibrating and validating the methods of detection and quantification described hereafter.…”
Section: Airborne Imagesmentioning
confidence: 99%
“…The RLR classifier was fitted on the training set and applied to the test set. Predictions made on the test set were evaluated using the overall accuracy (OA), Cohen's kappa coefficient, and confusion matrices [49,53,54]. The method was then validated on the other contaminated and control sites (n = 4 and 5 sites, respectively, Table 1).…”
Section: First Step Of the Approach: Detection Of Oil Contaminationmentioning
confidence: 99%